Strategi Pemerintah Dalam Meningkatkan Ketahanan Pangan Pada Masa Pandemi Di Kabupaten Majene - Taufik, Ahmad; Chaminra, Tipani; Utami, Isra Rezky; Isnaad, Ainia Dzikra Putri; Gaffar, Dian Ekawati; Rusman, Muhammad (Universitas Muhammadiyah Makassar, 2021)
This type of research uses qualitative research with the type of phenomenological research, namely examining a certain phenomenon that exists in society which is carried out in depth to study the background, circumstances, and interactions that occur about the government's strategy in improving food security during the current covid-19 pandemic in the district. Majene. The informant in this study was the secretary of the food security department of Majene Regency. The results of this study indicate that in the development and improvement of food security in Majene Regency, the government prioritizes the function of coordination with various related agencies and also community involvement. This increase in food security is an opportunity to improve the community's economy, so that a stable food industry can be realized that involves the community in managing and developing food security. However, based on the results of the study, realizing that the availability of food is not sufficient, community empowerment activities are carried out by the government / local agencies and provide counseling about food security efforts that can be done at home during this pandemic. One of them is by using the yard of the house to grow crops